EFFECTS OF IRRIGATION FREQUENCY AND LEAF DETACHMENT ON CHRYSANTHEMUM GROWN IN TWO TYPES OF PLASTIC HOUSE - K. Budiarto; Y. Sulyo; E. Dwi S.N.; R.H.M. Maaswinkel (Indonesian Agency for Agricultural Research and Development, 2007)
Chrysanthemum is one of important ornamentals in Indonesia and it ranks in the first quantity of cut flower marketed every year. In most cases, the low productivity is still a constraint for the traditional growers to make production process profitable. Several problems revealed in chrysanthemum production were investigated. The study dealt with the effect of two types of plastic house constructions, irrigation frequency, and leaf detachment on the growth and development of chrysanthemum. The experiment was conducted at Segunung, Indonesian Ornamental Plants Research Institute during the dry season of 2005. A nested design with six replications was used. The results showed that plants grown in wood-constructed plastic house had better growth performance and flower quality than those under bamboo plastic house. Longer stem and higher plant fresh weight with more flowers and longer life span were also observed on chrysanthemum irrigated four times per week than those irrigated twice per week. Leaf removal often practiced by the growers is no longer recommended, since the number of leaves on the plant influenced all parameters observed. The more leaves were detached, the more negative impacts on plant growth were found.